Sex trafficking screening and intervention in the emergency department: A scoping review. Issue 1 (15th January 2022) - Marcinkowski, Bridget; Caggiula, Amy; Tran, Brandon N.; Tran, Quincy K; Pourmand, Ali
Abstract: Introduction: Human sex trafficking is a global public health crisis. Emergency departments (EDs) are important access points for trafficked persons who seek medical care. However, because of victims' hesitancy to disclose their situation and health care practitioners' lack of training and institutional protocols, many trafficked persons go unrecognized. Methods: We performed a scoping review of current literature. PubMed, SCOPUS, and reference lists were searched to identify articles for inclusion. We aimed to identify gaps in knowledge and shortcomings to assist this vulnerable population. Two reviewers independently screened literature search results and abstracted data from included studies. Descriptive analysis was conducted. Results: We selected and analyzed 23 studies that focused on adult human sex trafficking identification, screening, interventions, or education in the ED. Eight (35%) of the publications used a survey model to quantitatively assess outcomes. Many of the other publications were descriptive or qualitative in nature, with some using a structured interview approach. We have observed that no validated or consistent screening tool exists for the identification of possible adult trafficked patients in the ED. However, we found that educational interventions and screening tools can improve health care practitioners' confidence, victim identification, and knowledge of "next steps" for victims. Conclusions: We found that most ED clinicians and staff have little or no formal training in sex trafficking victim identification, support, institutional protocols, or available local resources. Our review demonstrates a paucity of formal training programs, validated adult screening tools, and standardized institutional protocols to aid in the care of trafficked patients in the ED.